2016
DOI: 10.1007/s12011-016-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Induced Spermatozoa Head Malformation Is Related to Oxidative Damage to Testes in CD-1 Mice

Abstract: The molecular mechanism for copper toxicity on spermatozoa quality in mice is not well understood. In a 4-week experiment, we challenged 24, 6-week-old male CD-1 mice with twice-a-week intraperitoneal copper chloride injections and evaluated spermatozoa quality, copper levels in the testes, serum testosterone, the expression of key antioxidant glutathione peroxidase 5 (GPx5), and the regulated androgen receptor (AR) in the mice testes. We compared these outcomes for four groups of six mice given doses of 0, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Interestingly, we observed that the testicular Cu content was higher in the LG group than in the HG group, which may be related to the elevated expression of ATP7A and ATP7B in the testes, and similar results have been reported in other studies (Li et al 2021 ). Then, Cu exposure caused the decrease in testicular coefficient, testicular degeneration, and sloughing of spermatocytes in the testicular tissue, and these results were similar to previous reports (Zhang et al 2016 ; Chen et al 2020 ). Therefore, we speculate that the Cu exposure caused testicular toxicology probably because the high concentrations of Cu caused upregulated expression of testicular Cu transporters, resulting in Cu to accumulate in the testicular tissue, which damages the testis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we observed that the testicular Cu content was higher in the LG group than in the HG group, which may be related to the elevated expression of ATP7A and ATP7B in the testes, and similar results have been reported in other studies (Li et al 2021 ). Then, Cu exposure caused the decrease in testicular coefficient, testicular degeneration, and sloughing of spermatocytes in the testicular tissue, and these results were similar to previous reports (Zhang et al 2016 ; Chen et al 2020 ). Therefore, we speculate that the Cu exposure caused testicular toxicology probably because the high concentrations of Cu caused upregulated expression of testicular Cu transporters, resulting in Cu to accumulate in the testicular tissue, which damages the testis.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, serum T and PTH levels did not change in response to treatment with different concentrations of Cu. In other studies, serum T levels were significantly reduced by Cu treatment; however, it has also been found that Cu exposure does not affect serum T levels (Zhang et al 2016 ; Chen et al 2020 ). The LH and FSH can respectively induce proliferation of testicular Leydig cell and Sertoli cell, and LH additionally supports a normal increase in the testicular size (Wells et al 2013 ).…”
Section: Discussionmentioning
confidence: 87%
“…In some countries, copper sulfate (CuSO 4 ) has been widely used as a feed additive in animal production (2). However, copper overload could cause the tissue or organ damage in human and other mammals, affecting the liver, kidney, brain, lung, intestine, heart, and testis (3)(4)(5)(6)(7)(8)(9)(10). Over the past decades, Cu overload was suggested to be associated with the development of Wilson's disease and other neurodegenerative diseases, which has raised concerns worldwide (7,11).…”
Section: Introductionmentioning
confidence: 99%
“…All reactions were run in triplicate and data were analyzed according to the 2 −△△Ct method [Pfaffl 2001]. RT-PCR was performed as reported previously with LCN2 sequence-specific primers and GAPDH was used as the reference gene [Zhang et al 2016]. The corresponding primer sequences used for RT-PCR were listed in Table 1.…”
Section: Real-time Pcrmentioning
confidence: 99%